Fulfillment Of Constitutional Rights Of Persons With Disabilities Study Pohuwato Regency - Faisal Panggi; Sumiyati B; Rusmulyadi Rusmulyadi (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study aims to analyze the implementation of the fulfillment of the constitutional rights of persons with disabilities in obtaining employment in Pohuwato Regency. The right to work is guaranteed by the 1945 Constitution, Law Number 8 of 2016 concerning Persons with Disabilities, and Pohuwato Regency Regional Regulation Number 12 of 2023. This study employs an empirical legal research method with a qualitative approach. Data were obtained through observation, interviews, and documentation involving the Social Affairs Office, the Manpower and Transmigration Office, regional-owned enterprises, private companies, and persons with disabilities. The findings show that the fulfillment of employment rights for persons with disabilities has not been optimally implemented. Of the 1,010 persons with disabilities in Pohuwato Regency, only 8 have been absorbed into formal employment. This condition indicates a gap between legal norms and their practical implementation. The obstacles identified include weak data collection, limited job training, low company compliance, inadequate reasonable accommodation, and ineffective local government supervision. These findings affirm that regulations alone are insufficient without measurable implementation, consistent supervision, and employer commitment. This study recommends strengthening inclusive policies, job training, quota supervision, the provision of reasonable accommodation, and more sustainable and responsive cross-sectoral cooperation at the regional level.